COMPARATIVE ANALYSIS OF HOW MEDICAL/HEALTH DATA IS REGULATED UNDER GDPR (EU), HIPAA (USA), AND KAZAKH LAW. DATA PROTECTION CHALLENGES IN DENTAL CLINICS - Ussipbekova D.; Imasheva Z.; Abu Moamer Heba (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This article elucidates what risks dental clinics are at and explains the significance of being aware of all the challenges that can arise during the process of work by introducing the differences between international standards like the European GDPR and the American HIPAA compared to what is occurring in Kazakhstan. The goal of this investigation is to demonstrate the solutions and methods of adaptation of this practice in our country. The analysis of regulations harnessed overseas, national legislation, problems in practice are implemented as the basis for this study with the addition of a local survey conducted among students of the dental faculty to make them enlightened of the data protection principles and evaluate their current knowledge.
Keywords: cybersecurity; dental medicine; data protection; privacy; data leaks; legislation; international data security and standards